PERBEDAAN PERBEDAAN PENGARUH TANDEM GAIT EXERCISE DAN SQUARE STEPPING EXERCISE TERHADAP RESIKO JATUH PADA LANSIA - Yoni Rustiana Kusumawati (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2023)
Background: The increase in the elderly population from year to year will have an impact on increasing health problems for the elderly. Changes in the body functions of the elderly related to aging can affect physical and psychological health which in the future will affect the social and economy. One of the problems is the increased risk of falling caused by physiological changes in the body due to the aging process. For this reason, intervention is needed to deal with this problem. Tandem gait exercise and square stepping exercise can be used as an alternative as a form of preventive and rehabilitative action. The goal to be achieved in this study is to determine the difference in the effect of tandem gait exercise and square stepping exercise on the risk of falling in the elderly. Methods: Two Group Pre test – Post test Design. Measuring instrument : TUG test Results: independent t test by comparing the post test of the tandem gait exercise group and the square stepping exercise group obtained a value of p = 0.075 (p> 0.05) meaning that there is no difference between tandem gait exercise and square stepping exercise on the risk of falling in the elderly. Conclusion: there is no significant difference between tandem gait exercise and square stepping exercise on the risk of falling in the elderly.